Islamic state : ideological challenge to Saudi Arabia - James M. Dorsey (2014)
With its control of a swath of Iraq and Syria, the Islamic State represents a paradigm shift in jihadist strategy and tactics. It also poses an ideological challenge to Saudi Arabia as it fuels Salafist debate about political Islam and the legitimacy of thr region's rulers.